Flavokawain B Induced cytotoxicity in Two Breast Cancer Cell Lines, MCF-7 and MDA-MB231 and Inhibited the Metastatic Potential of MDA-MB231 via the Regulation of Several Tyrosine Kinases In vitro - Nadiah, Abu; Akhtar, Muhammad Nadeem; Swee, K. Yeap; Kian, Lam Lim; Wan, Yong Ho; Mohd Puad, Abdullah; Chai, Ling Ho; Abdul Rahman, Omar; Jamil, Ismail; Noorjahan Banu, Alitheen (BioMed Central Ltd., 2016)
Background